2021
DOI: 10.1186/s12933-020-01210-5
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride–glucose index is associated with the risk of myocardial infarction: an 11-year prospective study in the Kailuan cohort

Abstract: Background The triglyceride–glucose (TyG) index, which is a simple surrogate marker of insulin resistance, has been suggested as a contributor of cardiovascular disease. However, evidence on the effect of long-term elevation of the TyG index exposure on myocardial infarction (MI) is limited. The current study aimed to evaluate the association of baseline and long-term elevation of the TyG index exposure with the risk of MI. Methods A total of 98,84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 37 publications
5
113
2
Order By: Relevance
“…In addition, the levels of TG and LDL-C in the T2DM group were higher than those in the NC group. The free fatty acids produced by TG were able to further reduce insulin sensitivity, forming a vicious circle between TG levels and insulin resistance (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the levels of TG and LDL-C in the T2DM group were higher than those in the NC group. The free fatty acids produced by TG were able to further reduce insulin sensitivity, forming a vicious circle between TG levels and insulin resistance (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…(2) The study population was highly selected with strict enrollment criteria, which may result in selection bias and difficulties in generalizing the findings to other populations. (3) Despite dynamic changes [ 54 ] and the mean of multiple monitoring [ 55 ] of the TyG index during the follow-up having been proved to be closely associated with cardiovascular events, they were not accessible in the current analysis. Further group-based trajectory analysis is needed to provide more reliable findings.…”
Section: Discussionmentioning
confidence: 99%
“…The TyG index can also predict the risk of diabetes mellitus [39]. Many studies demonstrated that the TyG index is closely related to the prognosis of acute coronary syndrome [40][41][42]. Acute coronary syndrome, hypertension, diabetes mellitus and other factors can cause cardiac function and structural disorders, leading to heart failure [43].…”
Section: Discussionmentioning
confidence: 99%